SEEING THE BEAUTY IN COMPUTERS. - Delaney, John (Communications of the ACM, 2018)
The article discusses computer science professor Gail Murphy's perspective on the alleged beauty of computers, including in regard to her effort on behalf of increasing knowledge workers' productivity, computer software design and software development.